2018
DOI: 10.14198/jhse.2018.133.17
|View full text |Cite
|
Sign up to set email alerts
|

Continuous assessment and interactive response systems in higher education

Abstract: There is evidence that the use of information and communication technologies (ICTs) has the potential to improve assessment methods, and therefore, learning process and results. This study compares the effect of two different types of assessment on the learning results of university students: traditional continuous assessment (TCA) and continuous assessment with the interactive response system Educlick (CAE). A quasi-experimental study with 364 students of the degree in Primary Education was conducted. Partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Our study found that most students prefer continuous assessment modules instead of having to write an exam. This finding is in agreement with previous studies where students indicated preference for CA as opposed to just an exam (Rezigalla et al, 2017;González-Campos et al, 2018;Rana and Zubair, 2019;Sanz-Pérez, 2019). This preference helps students to avoid anxiety that often comes with having to write an exam (Bjaelde et al, 2017).…”
Section: Perception Of Students On Continuous Assessmentsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study found that most students prefer continuous assessment modules instead of having to write an exam. This finding is in agreement with previous studies where students indicated preference for CA as opposed to just an exam (Rezigalla et al, 2017;González-Campos et al, 2018;Rana and Zubair, 2019;Sanz-Pérez, 2019). This preference helps students to avoid anxiety that often comes with having to write an exam (Bjaelde et al, 2017).…”
Section: Perception Of Students On Continuous Assessmentsupporting
confidence: 92%
“…The application of CA in higher education spans different disciplines (Rezigalla et al, 2017;Day et al, 2018c;Nayak et al, 2020;Zhan, 2020) and various pedagogic approaches (Day et al, 2018b;Llamas-Nistal et al, 2019;Chong et al, 2020). CA has also been shown to work in traditional contexts as well as through using online and interactive Information and Communications Technology (ICT) systems (González-Campos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that the use of information and communication technologies has the potential to improve assessment methods, and therefore, learning process and students' results in PE (González-Campos et al, 2018). The average academic grade of our research participants is not a high grade.…”
Section: Discussionmentioning
confidence: 81%
“…Information collection can be done in multiple ways. There are four assessment terms known, namely traditional assessment, assessment, performance assessment, and authentic assessment, with a simple description as shown in Table 6 (Bakhru & Mehta, 2020;González-Campos et al, 2018;Morales et al, 2022;Sridharan, 2016). Table 6.…”
Section: Discussionmentioning
confidence: 99%
“…Compiling the outcome should not be separate from the lectures taken during the study. Likewise, the implementation of the assessment should also be carried out in an integrated and sustainable manner (Day et al, 2018;Dejene & Chen, 2019;Durovic et al, 2020;González-Campos et al, 2018;Llamas-Nistal et al, 2019;Martínez et al, 2020;Sánchez-Ruiz et al, 2021). Students must be able to find real problems, which will be solved according to their competence.…”
Section: Introductionmentioning
confidence: 99%